PENGEMBANGAN E-JOBSHEET BERBASIS LIVEWORKSHEETS PADA MATA PELAJARAN DASAR-DASAR TEKNIK GEOSPASIAL - Sutrisno, Sutrisno; Marpaung, Suci Febriyanti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT This research was motivated by the need for engaging and interactive learning media to support the learning process in the subject of Basic Geospatial Engineering. This study aims to analyze the development stages and feasibility of e-jobsheet products with the liveworksheets application used in the Basics of Geospatial Engineering subject for class X Geomatics Engineering 1 students in the odd semester of the 2025/2026 academic year at Vocational High School 1 of Percut Sei Tuan. The research employed a Research and Development (R&D) approach using the 4D development model, which was modified into three stages, namely Define, Design, and Develop. The instrument used was a questionnaire. The questionnaire was used to test the feasibility of the e-jobsheet through validation by material experts and media experts. The results showed that the developed e-jobsheet received an average score of 4.39 from material experts (categorized as “highly feasible”) and an average score of 4.20 from media experts (categorized as “highly feasible”). Therefore, the development of an e-jobsheet using the liveworksheets application is considered highly feasible for use by Grade X Geomatics Engineering students at Vocational High School 1 of Percut Sei Tuan. ABSTRAK Latar belakang penelitian ini didasari oleh kebutuhan akan media pembelajaran yang menarik dan interaktif dalam mendukung proses pembelajaran pada mata pelajaran Dasar-Dasar Teknik Geospasial. Penelitian ini bertujuan untuk menganalisis tahapan pengembangan dan kelayakan produk e-jobsheet dengan aplikasi liveworksheets yang digunakan pada mata pelajaran Dasar-Dasar Teknik Geospasial untuk peserta didik kelas X Teknik Geomatika 1 semester ganjil tahun ajaran 2025/2026 di SMK Negeri 1 Percut Sei Tuan. Metode penelitian yang digunakan adalah Research and Development (R&D) dengan model pengembangan 4D yang dimodifikasi menjadi 3D (Define, Design, Develop). Instrumen yang digunakan berupa angket. Angket digunakan untuk menguji kelayakan e-jobsheet melalui validasi ahli materi dan ahli media. Hasil penelitian menunjukkan bahwa produk e-jobsheet yang dikembangkan memperoleh nilai rata-rata dari ahli materi sebesar 4,39 (kategori “sangat layak”), serta memperoleh nilai rata-rata dari ahli media sebesar 4,20 (kategori “sangat layak”). Dengan demikian pengembangan e-jobsheet dengan aplikasi liveworksheets menurut para ahli sangat layak digunakan peserta didik kelas X Teknik Geomatika di SMK Negeri 1 Percut Sei Tuan.